2020
DOI: 10.1038/s41377-020-00432-2
|View full text |Cite
|
Sign up to set email alerts
|

Dirac-vortex topological photonic crystal fibre

Abstract: The success of photonic crystal fibres relies largely on the endless variety of two-dimensional photonic crystals in the cross-section. Here, we propose a topological bandgap fibre whose bandgaps along in-plane directions are opened by generalised Kekulé modulation of a Dirac lattice with a vortex phase. Then, the existence of mid-gap defect modes is guaranteed to guide light at the core of this Dirac-vortex fibre, where the number of guiding modes equals the winding number of the spatial vortex. The single-vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7]. Topological one-way edge state provides a powerful platform for novel photonic devices with nontrivial functionalities and excellent performances, such as one-way waveguide [8][9][10][11][12], topological laser [13][14][15][16][17], rainbow trapping phenomenon [18][19][20][21], dispersionless slow light [22][23][24], topological fibre [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7]. Topological one-way edge state provides a powerful platform for novel photonic devices with nontrivial functionalities and excellent performances, such as one-way waveguide [8][9][10][11][12], topological laser [13][14][15][16][17], rainbow trapping phenomenon [18][19][20][21], dispersionless slow light [22][23][24], topological fibre [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…n recent years, topological edge states in photonic systems have attracted considerable attention owing to their robustness to scattering and defects as well as reliable edge transmission [1], [2]. They have been widely used in the fields of integrated photonics and fiber optics to improve the beam transmission capacity of photonic crystals [3]- [5] and improve the quality factor of optical microcavities [6], or to achieve realtime detection of biological molecules [7]. Recently, there has been rapid progress in hollow-core photonic bandgap fiber (HC-PBF), which has emerged as an increasingly attractive and credible alternative to all-solid fibers in various applications [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…TPSs have been theoretically proposed and experimentally demonstrated in different photonic systems, such as gyromagnetic photonic crystals (GPCs) (Wang et al, 2008;Wang et al, 2009;Fu et al, 2010;Poo et al, 2011), all dielectric structures (Chen et al, 2017;Dong et al, 2017;Chen et al, 2018;He et al, 2019), non-linear systems (Leykam and Chong, 2016;Kruk et al, 2017;Dobrykh et al, 2018;Kruk et al, 2018;Smirnova et al, 2019;Zangeneh-Nejad and Fleury, 2019;Smirnova et al, 2020), and metamaterials (Gao et al, 2015;Yang et al, 2018;Jia et al, 2019). Various novel physical concepts and applications related to TPSs have also been presented, for example, topological laser (Bahari et al, 2017;Bandres et al, 2018;Harari et al, 2018;Shao et al, 2020;Zeng et al, 2020), topological fiber (Lu et al, 2018;Lin and Lu, 2020), topological delay line (Yang et al, 2013;Chen et al, 2019a;Chen et al, 2019b;Chen et al, 2020;Shi et al, 2021), topological light routing (Chen et al, 2021b), and three-dimensional topological photonic insulator (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%